2019
DOI: 10.1016/j.biortech.2019.121521
|View full text |Cite
|
Sign up to set email alerts
|

Strategic intensification in butanol production by exogenous amino acid supplementation: Fermentation kinetics and thermodynamic studies

Abstract: Highlights Exogenous addition of tryptophan:phenylalanine triggered butanol production  Amino acid addition after 8 h in batch cultivation resulted in 12.43±0.1g/L butanol  Fed-batch with in-situ product recovery was promising for improved butanol titer  ABE production follow first order kinetics in respect to intermediate concentration  Thermodynamics of ABE fermentation was studied to evaluate reaction feasibility Abstract Amino acids are vital precursors in many biochemical production pathways in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our recent study described that tryptophan drives more metabolic flux toward butanol, while arginine could be useful in energy (ATP) build up. 38 Moreover, it has been demonstrated that pelleting soybean meal with calcium lignosulfonate protects protein degradation in the rumen. 39 Similarly, lignosulfonates might be coupled with added soy meal and result in a lowered inhibitory effect in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study described that tryptophan drives more metabolic flux toward butanol, while arginine could be useful in energy (ATP) build up. 38 Moreover, it has been demonstrated that pelleting soybean meal with calcium lignosulfonate protects protein degradation in the rumen. 39 Similarly, lignosulfonates might be coupled with added soy meal and result in a lowered inhibitory effect in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, tryptophan and arginine also have a positive role in ABE fermentation. Our recent study described that tryptophan drives more metabolic flux toward butanol, while arginine could be useful in energy (ATP) build up . Moreover, it has been demonstrated that pelleting soybean meal with calcium lignosulfonate protects protein degradation in the rumen .…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids and their derivatives serve as crucial precursors in various metabolic pathways and play significant roles in microbial metabolism and function ( Nimbalkar et al, 2019 ). In a study conducted by Gomes et al (2020) , it was found that aspartic acid, phenylalanine, and serine enhanced BC production in a static culture environment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the metabolic pathway and physiological characteristics, various organic acids (such as acetate, butyrate, amino acids, and lactic acid) could serve as alternative substrates for butanol production, and then maintain the robust expression of enzymes associated during the solventogenic and solventogenesis phase [169,170]. Interestingly, when butyrate was the sole carbon source, only 0.2 g/L of butanol was produced, but the production of butanol significantly increased to 10 g/L when both butyric acid and glucose were present, suggesting that butyric acid may be an important factor triggering solvent production [171].…”
Section: Optimization Of Culture Conditions Effects Of Exogenous Addimentioning
confidence: 99%